PENGARUH PENAMBAHAN GLOVE DAN PENGURANGAN YEHUDI SERTA PERGESERAN LOKASI APEX TERHADAP KARAKTERISTIK AERODINAMIKA SAYAP PESAWAT TERBANG - Sudira, I G.N (BRIN Publishing, 2011)
Success indicator in airplane design process is depended on success or not in wing design process. Wing design process was supported by many design variable and the final result was compromise one from many scientific science or specialist. The first step in airplane wing design after design requirement & objective (DR&O) was defined, is determining wing planform through parametric study. Parametric study was conducted to make sure that all design parameters have been considered especially for aerodynamic and structural aspect. This paper discuses the influence of glove and yehudi changes and also apex location movement with respect to aerodynamic characteristic of the wing. Additional of the glove was intended to compensate yehudi existent due to structural aspect mainly for landing gear placement. Disadvantage of aerodynamics aspect due to yehudi existent is expected will be overcome by additional of glove. Apex location is also important parameter to control the shape of pressure coeffient of wing profile. Apex location can be moved according to sensitivity of designer to achieve design target. For the whole, it can be said that glove and yehudi and also apex location can be isolated its influence to major variable design namely to wing profile pressure distribution. The computer program used in this analysis is integration of the program for wing geometry generation, paneling process and computational fluid dynamic code (CFD), in this case VSAERO, and by author it is called NWDU.